THE CONCEPT OF THE HISTORY OF ANCIENT UKRAINIAN ART IN THE CONTEXT OF DEVELOPMENT ARCHAEOLOGICAL SCIENCE LATE XIX - EARLY XX CENTURY (Pedagogy of Higher and Secondary Education, 2022)
Becoming of conception of history of ancient Kiev's art in the context of elaboration of archaeological science at end of the XIX and beginning of the XX century. In the article is explained the problem of becoming of scientific conception of history of domestic art. The publications are examined on the indicated problem of leading specialists of that epoch in Labours o f archaeological conventions at end of the XIX and beginning of the XX century as an information base for explaining of historiogyraphy questions in researches of different aspects of history o f the Ukrainian art.
Keywords: master's degree artistically-pedagogical education; history of study of art; archeology